MODERN APPROACHES FOR DETECTING DATA LEAKAGE PROBLEMS (International Journal of Engineering and Computer Science, 2017)
In Organizations, detecting data leaker is facing many difficulties to find who cause for the data leakage. In previous approaches there are many techniques to find the leaker using fake objects and how much data leaked. In this paper, we present S-Random, S-Optimal, E-Random and E-Optimal techniques to find the (leaker). In this, we assigning the data with addition of fake objects through that, if the data is leaked then fake objecthelp to find the particular by using E-Random and S-Random techniques.It improves the efficiency for finding the leaker.